Plasma Ceramides and Sphingomyelins in Relation to Atrial Fibrillation Risk: The Cardiovascular Health Study. Issue 4 (18th February 2020) - Jensen, Paul N.; Fretts, Amanda M.; Hoofnagle, Andrew N.; Sitlani, Colleen M.; McKnight, Barbara; King, Irena B.; Siscovick, David S.; Psaty, Bruce M.; Heckbert, Susan R.; Mozaffarian, Dariush; Sotoodehnia, Nona; Lemaitre, Rozenn N.
Abstract : Background: Ceramides exhibit multiple biological activities that may influence the pathophysiological characteristics of atrial fibrillation (AF). Whether the length of the saturated fatty acid carried by the ceramide or their sphingomyelin precursors are associated with AF risk is not known. Methods and Results: Among 4206 CHS (Cardiovascular Health Study) participants (mean age, 76 years; 40% men) who were free of prevalent AF at baseline, we identified 1198 incident AF cases over a median 8.7 years of follow‐up. We examined 8 sphingolipid species: ceramide and sphingomyelin species with palmitic acid and species with very‐long‐chain saturated fatty acids: arachidic; behenic; and lignoceric. In adjusted Cox regression analyses, ceramides and sphingomyelins with very‐long‐chain saturated fatty acids were associated with reduced AF risk (ie, per 2‐fold higher ceramide with behenic acid hazard ratio, 0.71; 95% CI, 0.59–0.86; sphingomyelin with behenic acid hazard ratio, 0.60; 95% CI, 0.46–0.77). In contrast, ceramides and sphingomyelins with palmitic acid were associated with increased AF risk (ceramide with palmitic acid hazard ratio, 1.31; 95% CI, 1.03–1.66; sphingomyelin with palmitic acid hazard ratio, 1.73; 95% CI, 1.18–2.55). Associations were attenuated with adjustment for NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide), but did not differ significantly by age, sex, race, body mass index, or history of coronary heart disease. Conclusions: Our findings suggest that several ceramide and sphingomyelin species are associated with incident AF, and that these associations differ on the basis of the fatty acid. Ceramides and sphingomyelins with palmitic acid were associated with increased AF risk, whereas ceramides and sphingomyelins with very‐long‐chain saturated fatty acids were associated with reduced AF risk.